Symbolic Representation of the Bangkat War in the Osing Tribe Manten Gathering Procession from a Semiotic Perspective - Dewi Anggraini; Siti Nur Afifatul Hikmah (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2026)
This study aims to analyze the representation of symbolic meaning in the Perang Bangkat procession in the Temu Manten series of the Osing Tribe through a semiotic perspective. The study used a qualitative method with a field research approach. Data was obtained through participatory observation, semi-structured interviews with traditional leaders and procession participants, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman which includes data reduction, data presentation, and conclusion drawing. The results show that Perang Bangkat is a cultural text containing a system of signs in the form of icons, indexes, and symbols that represent social readiness, moral responsibility, self-control, equal roles between husband and wife, and harmony in the married life of the Osing people. This procession is not interpreted as a physical conflict, but rather as a symbolic medium to transmit values and philosophies of life collectively. This study contributes to strengthening the study of cultural semiotics through the analysis of verbal and nonverbal signs in local traditions and supports the preservation of Osing cultural meaning amidst social change.